EPIDEMIOLOGY OF COVID-19 AND RISK FACTORS OF COVID-19 INFECTIONS IN PULAU PINANG: A CASE CONTROL STUDY - Bin Hamedin, Mohamad Afiq Amsyar; Rozaini Binti Mat Shah; Marina Binti Kamardin (Malaysian Journal of Public Health Medicine, 2022)
Emergence of COVID-19 (Coronaviruses Disease 2019) has been brought to global concern. Malaysia has reported 6002 cases with 102 deaths as of 30th April 2020.While predictor for mortality for COVID-19 can be common in many countries, risk factors for COVID-19 infections in any outbreak can be different according to various locations and population background. The aim of this study was to describe epidemiology and risk factors of COVID-19 infections in state of Pulau Pinang, Malaysia. A case control study was conducted using secondary data obtained from State Health Department of Pulau Pinang COVID-19 registry. Analysis included 107 confirmed cases and 535 contacts of COVID-19 infection from 5th Match 2020 till 30th April 2020 forming ratio case to control 1:5. Result showed prevalence of COVID-19 infection during study period was 4.6%. Multivariate analysis showed adult age group had 7.35 higher odd of getting COVID-19 infection (aOR= 7.35, 95% CI 1.97,27.33, p=0.003) compared with other age groups. Meanwhile, symptomatic individuals had 8.72 higher odds of getting COVID-19 infection (aOR= 8.72, 95% CI 4.67, 16.25, p=0.001). Person attending mass events with COVID-19 positive individuals had 4-time higher odds of getting COVID-19 infections (aOR= 4.39, 95% CI 1.39,13.86, p=0.012). Study findings supported the current practices of COVID-19 outbreak management which are mandatory quarantine all identified close contacts, prioritize contacts with symptoms for screening and prohibiting mass gathering as major part of control measures in the country.